DETERMINATION OF THE OCTANE NUMBER OF AUTOMOTIVE GASOLINES BY FTIR SPECTROMETRY WITH CHEMOMETRICS (Perner's Contacts, 2022)
The quality of motor fuels is more and more strictly controlled in connection with many factors - users are particularly interested in the anti-knock resistance of automotive gasolines, quantitatively expressed by the value of the research octane number (RON). The paper presents FTIR spectrometry in conjunction with chemometry as an alternative method to the standardized determination of the octane number of gasoline by a research method according to ČSN EN ISO 5164. An FTIR-PLS regression model working with spectra in the range of 650–4000 cm-1 was proposed for ON prediction. With this model, a very strong dependence (R=0.996) was achieved between the predicted of octane number values and the values determined by the standardized method; the calibration error was 0.414.
Keywords: octane number; gasoline; fuels; measurement; quality; FTIR spectrometry; chemometric model